Research in organizational change and development. Vol. 13 - Woodman, Richard W.; Pasmore, William A. (Emerald, 2001)
The theoretical frames outlined in this volume on research in organizational change and development range from perspectives so new that they are relatively undeveloped (for example chaos theory), to perspectives and ideas that have been in widespread use for many years (such as action research). The focus of these articles range from challenging the traditional action research paradigm, to debating the need for greater professionalization in OD. In addition, the volume grapples with the difficult problems of downsizing and organizational turnaround, and avoiding the associated problems resulting from flattened organizational structures, to implementing changes in information technology to realize the promised increased effectiveness.
Keywords: Organizational change.; elektronické knihy; electronic books